Museum space and the experience of the sacred - Buggeln, Gretchen Townsend (Material religion, 2012)
This essay explores the dichotomous way we talk about and experience the sacred in art museum space. While Western museum culture has generally encouraged the notion of the museum visit as a quasi-religious, even transcendent, aesthetic encounter with art and architecture, it has shunned particular and obvious expressions of religious devotion. Why is a certain understanding of "sacred space" permissible, while other meanings of that term seem to make museum professionals uncomfortable? Using numerous examples, this essay first considers museum space and the way we have come to talk about it, paying particular attention to the evolution from classical to modern architecture and the effect that has had on the museum experience. It then considers the treatment of religious artifacts and cultures in museum spaces and how this might be changing today, as museums deliberately pursue exhibitions with a more ambitious social agenda, one with contemporary religious content and relevance. The author uses Stephen Greenblatt's formulation of two contrasting modes of museum experience, "resonance" and "wonder," to think through varying dimensions of visitor response, and suggests how a sacred/not sacred tension in Western museums is a product of specific historical relationships between culture, art, and museums.